If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + 9x = 10x + -2 Reorder the terms: 60 + 9x = -2 + 10x Solving 60 + 9x = -2 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 60 + 9x + -10x = -2 + 10x + -10x Combine like terms: 9x + -10x = -1x 60 + -1x = -2 + 10x + -10x Combine like terms: 10x + -10x = 0 60 + -1x = -2 + 0 60 + -1x = -2 Add '-60' to each side of the equation. 60 + -60 + -1x = -2 + -60 Combine like terms: 60 + -60 = 0 0 + -1x = -2 + -60 -1x = -2 + -60 Combine like terms: -2 + -60 = -62 -1x = -62 Divide each side by '-1'. x = 62 Simplifying x = 62
| (26-2x)(23-2x)=208 | | 3x-6y-42y-140x= | | 16+3x=4x | | 5ln(t+4)=5 | | (2x+3)(2x^2-13x+20)=0 | | 18+5x=7x | | 0=1/2dqrtx | | Z-4(2z+3)=15 | | 5ln(t-4)=5 | | -10=4-7x/3 | | -sin(x)+5cos(x)=4 | | (26-2x)(25-2x)=380 | | 17=2(3x+1)-6 | | 6x+5-2x=4x+4+1 | | i(2-6i)-(4+3i)= | | t-7/6=5/6 | | -3(t-5)+5t=7t-6 | | 5/12=1/3x | | 3x+1.5y=18 | | 3ln(3x)+5=17 | | 1+9(x-4)=7-9(x-5) | | 2(3x-7)-36= | | ((6x^3)-2x-5)(4x-1)= | | x^3+10x^2+14x=0 | | 8x-20+12-21x=80+48x | | -3.4(y-4)-4.4y= | | 33x+20y=450 | | 6(25/27)= | | 6(25/27) | | 6x+2(3-x)=7x+9+9 | | 6x+2(3-x)=6x+3+15 | | 6x+2(3-x)=7x+5 |